Structural breaks in finance growth nexus: the study of Indonesia - Mukhopadhyay, Bidisha (Journal of Economics and Behavioral Studies, 2011)
This paper empirically investigates the finance-growth nexus for an annual data set of Indonesia during the last two decades. The purpose is to examine the causal relationship between financial development and economic growth in Indonesia and also to test the structural breaks in the finance-growth relationship to investigate the change in policy regimes. To examine the causal relationship between financial development and economic growth, the newly proposed ARDL bound testing approach by Pesaran et al. (1996) has been applied .The estimated results support the view of Lucas (1988) that finance doesn’t matter for economic growth. Structural break is identified in the year 1997 in Indonesia with the estimated finance-growth relationship. The stability of the estimated relationship is examined with break-point Chow tests (F tests).